FINANCIAL INSTRUMENTS FOR SOCIAL INFRASTRUCTURE DEVELOPMENT OF THE REGION IN CONDITIONS OF DECENTRALIZATION - A. M. Revko; A. V. Verbytska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Non-governmental organizations have a potential to meet social needs and perform important civil tasks. Non-governmental organizations make a significant impact to the social life in Poland. They perform activities that provide social infrastructure development of the regions. The cooperation between governmental and non-governmental sector in Poland have different forms. Some of them could be adapted to Ukrainian decentralization conditions. In this connection, studying Polish experience in order to find financial instruments for social infrastructure development of the region in the conditions of decentralization of Ukraine is prospective. As education is one of the most powerful instruments for social infrastructure development and sustainable economic growth, educational projects have been analyzed in the paper in the context of financial cooperation between authorities and non-governmental sector.